Echocardiographic parameters associated with less reverse left ventricular remodeling after transcatheter aortic valve implant in subjects with prosthesis patient mismatch. - Peters, Andrew C.; Gong, Fei Fei; Ramesh, Ashvita; Andrei, Adin; Jankowski, Madeline; Cantey, Eric; Chen, Vincent; Thomas, James D.; Flaherty, James D.; Malaisrie, S. Christopher; Maganti, Kameswari (Echocardiography, 2024)
Background: Transaortic valve implant (TAVI) is the treatment of choice for severe aortic stenosis (AS). Some patients develop prosthesis patient mismatch (PPM) after TAVI. It is challenging to determine which patients are at risk for clinical deterioration. Methods: We retrospectively measured echocardiographic parameters of left ventricular (LV) morphology and function, prosthetic aortic valve effective orifice area (iEOA) and hemodynamics in 313 patients before and 1 year after TAVI. Our objective was to compare the change in echocardiographic parameters associated with left ventricular reverse modeling in subjects with and without PPM. Our secondary objective was to evaluate echo parameters associated with PPM and the relationship to patient functional status and survival post‐TAVI. Results: We found that 82 (26.2%) of subjects had moderate and 37 (11.8%) had severe PPM post‐TAVI. There was less relative improvement in LVEF with PPM (1.9 ± 21.3% vs. 8.2 + 30.1%, p =.045). LV GLS also exhibited less relative improvement in those with PPM (13.4 + 34.1% vs. 30.9 + 73.3%, p =.012). NYHA functional class improved in 84.3% of subjects by one grade or more. Echocardiographic markers of PPM were worse in those without improvement in NYHA class (mean AT/ET was.29 vs..27, p =.05; DVI was.46 vs..51, p =.021; and iEOA was.8 cm/m2 vs..9 cm/m2, p =.025). There was no association with PPM and survival. Conclusions: There was no improvement in LVEF and less improvement in LV GLS in those with PPM post‐TAVI. Echocardiographic markers of PPM were present in those with lack of improvement in NYHA functional class.